Perinatal mortality or severe neonatal encephalopathy among normally formed singleton pregnancies according to obstetric risk status:" is low risk the new high risk?" A population-based cohort study. (September 2018) - Joyce, Niamh M.; Tully, Elizabeth; Kirkham, Colin; Dicker, Patrick; Breathnach, Fionnuala M.
Abstract: Objective: To evaluate the capacity of the current system of obstetric risk stratification at the outset of pregnancy to predict severe adverse perinatal outcome. Study Design: This retrospective cohort study of singleton pregnancies over a five year period (2009–2013) was performed at the Rotunda Hospital, Dublin, Ireland. High-risk or low-risk status was assigned retrospectively to a large consecutive cohort of women with a normally-formed singleton pregnancy on the basis of factors analyzed at the first prenatal hospital visit. The incidence of severe perinatal morbidity and mortality were compared between high- and low-risk groups to determine the predictive utility of risk stratification at the outset of pregnancy for severe perinatal morbidity. Results: During the study period, 41, 044 patients registered for prenatal care. 25, 702;(63%) were deemed low-risk and 15, 342;(37%) high-risk. Low-risk women were statistically more likely to be nulliparous (p < 0.0001) and to have a spontaneous or operative vaginal delivery (p < 0.0001). High-risk women were more likely to be multiparous and to undergo Caesarean delivery (p < 0.0001). The perinatal mortality rate was 3.8 per-1000 in low-risk pregnancies and 6.1 per-1000 in the a priori high-risk group (p = 0.012). The incidence of severe neonatal encephalopathy (NNE) was 1.8 and 0.65 per-1000 in the low and high-risk groups respectively (p = 0.0025). Conclusion: Where low-risk status is assigned at registration, neonatal encephalopathy is more prevalent. This data is relevant for the design of prenatal care models and demonstrates that assignment of low obstetric risk on the basis of maternal or pre-pregnancy factors alone may erroneously be interpreted as conferring low-risk status to the fetus.